Cathelicidin LL37 Promotes Osteogenic Differentiation in vitro and Bone Regeneration in vivo - Li, Lunhao; Peng, Yiyu; Yuan, Qingyue; Sun, Jing; Zhuang, Ai; Bi, Xiaoping (Frontiers in Bioengineering and Biotechnology, 2021)
Different types of biomaterials have been used to repair the defect of bony orbit. However, exposure and infections are still critical risks in clinical application. Biomaterials with characteristics of osteogenesis and antibiosis are needed for bone regeneration. In this study, we aimed to characterize the antimicrobial effects of cathelicidin-LL37 and to assess any impacts on osteogenic activity. Furthermore, we attempted to demonstrate the feasibility of LL37 as a potential strategy in the reconstruction of clinical bone defects. Human adipose-derived mesenchyme stem cells (hADSCs) were cultured with different concentrations of LL37 and the optimum concentration for osteogenesis was selected for further in vitro studies. We then evaluated the antibiotic properties of LL37 at the optimum osteogenic concentration. Finally, we estimated the efficiency of a PSeD/hADSCs/LL37 combined scaffold on reconstructing bone defects in the rat calvarial defect model. The osteogenic ability on hADSCs in vitro was shown to be dependent on the concentration of LL37 and reached a peak at 4 ug/ml. The optimum concentration of LL37 showed good antimicrobial properties against Escherichia coli and Staphylococcus anurans. The combination scaffold of PSeD/hADSCs/LL37 showed superior osteogenic properties compared to the PSeD/hADSCs, PSeD and control groups scaffolds, indicating a strong bone reconstruction effect in the rat calvarial bone defect model. In Conclusion, LL37 was shown to promote osteogenic differentiation in vitro as well as antibacterial properties. The combination of PSeD/hADSCs/LL37 was advantageous in the rat calvarial defect reconstruction model, showing high potential in clinical bone regeneration.